Պանթյուրքականության խնդիրը Իրանի Իսլամական Հանրապետությունում 2005-2013 թթ․ - Պետրոսյան, Լիանա (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Ethnic nationalism is an important component of the internal political life of any country, given the need to strengthen the internal security of that country, and in the case of Iran, being also at the crossroads of civilizations and ethnic groups. The activities of ethnic nationalists in western and southwestern Iran, where the economic and religious situation is markedly different from other Iranian provinces, and the potential for provocations by foreign forces in those areas may be significant. The situation is exacerbated by the existence of so-called "irredentism". On the one hand, Iran has the opportunity to influence its neighbors, but on the other hand, its neighbors can incite their target ethnic group to inter-ethnic clashes in Iran. In the context of the above, the issue of pan-Turkism in Iran is an important subject of discussion, which refers to the now Turkic-speaking historical Aturpatakan region, where activists try to promote pan-Turkic aspirations, mainly as foreign actors, with the ultimate goal of secession of this ancient land from Iran. It should be noted that the ethnic consciousness of this group is mainly determined not by the circumstance of linguistic affiliation, Turkish speaking, but by religious affiliation, the factor of being Shia. It is important in terms of ethnic self-awareness, forming an identity that can be defined by the term "Turkic-speaking Iranian". However, it should be noted that the Iranian authorities are in full control of the situation. Attempts at mass actions and protests are suppressed, activists are arrested, and the socio-political activities of NGO leaders are monitored. As for the neighboring countries, Iran had its own levers of pressure on the internal situation of those countries, such as the Shiite factor in Azerbaijan, the threat of exporting the Islamic Revolution, and ethnic conflicts in Turkey, which allowed Iran to maintain the balance of power.
Keywords: Պատմություն